Environmental regulation and firm exports: Evidence from the eleventh Five-Year Plan in China - Shi, Xinzheng; Xu, Zhufeng (Journal of environmental economics and management, 2018)
Combining time variations, cross-province variations in policy intensity, and variations in pollution intensity across industries, we estimate the impact of environmental regulation on firm exports. We find that in more pollution-intensive industries, stricter environmental regulation reduces both the probability that a firm will export and the volume of exports. Heterogeneous tests show that the impact is smaller for SOE firms and for firms located in the central and western part of China. We also find that the reduced probability that a firm will export is driven by a decline in non-exporters entering the export market.